Human histone demethylase KDM6B can catalyse sequential oxidations. Issue 57 (2nd July 2018) - Hopkinson, Richard J.; Langley, Gareth W.; Belle, Roman; Walport, Louise J.; Dunne, Kate; Münzel, Martin; Salah, Eidarus; Kawamura, Akane; Claridge, Timothy D. W.; Schofield, Christopher J.
Abstract : Biochemical studies on the histone lysyl demethylase KDM6B reveal it is capable of catalysing reactions on multiple lysine analogues, forming de-alkylated, hydroxylated, and oxidised products. Abstract : Jumonji domain-containing demethylases (JmjC-KDMs) catalyse demethylation of N ε -methylated lysines on histones and play important roles in gene regulation. We report selectivity studies on KDM6B (JMJD3), a disease-relevant JmjC-KDM, using synthetic lysine analogues. The results unexpectedly reveal that KDM6B accepts multiple N ε -alkylated lysine analogues, forming alcohol, aldehyde and carboxylic acid products.